Inisiasi Pembentukan Demonstrasi Plot Area Kampung Kelor Untuk Pencegahan Stunting - NUR Chabibah; Rini Kristiyanti; Milatun Khanifah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Stunting can cause an influence that greatly inhibits physical, mental and thinking growth which will ultimately reduce work productivity. Previous research has shown that “Kelor” tree (Moringa oleifera) has improved the nutritional status of children with Protein Energy Malnutrition (PEM). The desire of the community to create a stunting free society needs to be supported by the active role of the institution. The purpose of this activity is to facilitate the community in the formation of kelor villages. The formation of the kelor village is expected to increase the nutritional intake of toddlers. The methods include socializing the results of research on the benefits and nutritional value of Moringa plants, approaching cross-sector partners in the formulation of cooperation in establishing kelor villages, analyzing locations, seeding stages, planting stages, maintenance stages, monitoring and evaluating activities and making follow-up plans for training in making post-harvest products. The level of community service in the form of increasing knowledge about the nutritional value and benefits of Moringa plants, the existence of cross-sector cooperation in the formation and maintenance of kelor villages, the establishment of kelor villages and increasing community skills in utilizing and processing Moringa crop yields.